Are older adults with hip fractures a specific risk group for vitamin B12 deficiency?. Issue 2 (1st April 2022) - Dinamarca‐Montecinos, José Luis; Vásquez‐Leiva, Alejandra
Abstract: Background: Hip fractures (HF) are a high‐impact geriatric syndrome. Vitamin B12 deficiency is an HF risk factor. There are few studies on prevalence of B12 deficiency in older adults with HF. The objectives are as follows: in older adults with HF, to describe/characterize plasma levels of vitamin B12 (PL‐B12); to verify presence/absence of a subgroup with borderline, near‐deficient PLB12; to describe HF incidence; and to analyse relationships between PL‐B12 and studied variables. Methods: Cross‐sectional, observational study, analytical component. Complete Collection sample (01.08.2016–31.08.2018). Variables: PL‐B12, age, sex, HF location, time of year, in‐hospital stay length. Medians/percentiles, non‐parametric tests. PL‐B12 cut‐off points according to the WHO, proposing new cut‐off points to capture borderline values. Results: A total of 580 subjects. HF incidence = 264/100 000 ≥ 65 years, 79% female, 72% extracapsular HF. Medians: age = 83 years; PL‐B12 = 349 pg/cc; hospitalization = 13 days. Significantly lower PL‐B12 in males ( P = 0.023) and extracapsular fractures ( P = 0.013). No significant differences between age groups, length of hospitalization, and season of the year. Thirty‐five per cent B12 deficiency (16% deficiency and 19% mild deficiency). By increasing cut‐off point for deficiency to 400 pg/cc, prevalence increased to 58%. Conclusions: High prevalence of vitamin B12 deficiency among older adults with HF, significantly higher in men and extracapsular HF. Twenty‐four per cent normal PL‐B12 according to WHO criteria, but with borderline, near‐deficient levels, at the time of HF. In older adults with HF, we recommend measuring PL‐B12 and raising the cut‐off level required to diagnose deficiency. We consider that older adults with HF are a specific risk group for vitamin B12 deficiency.